The use of magnetic resonance imaging techniques in assessing the effects of alcohol consumption and heavy drinking on the adolescent brain: A scoping review protocol - Hornsby, N.; Seedat, S.; Westman, E.; Wahlund, L.O.; Siegfried, N.; Erasmus-Claassen, L.A.; Myers-Franchi, Bronwyn (MDPI, 2021)
Introduction: Alcohol consumption, specifically heavy drinking during adolescence, has been shown to be accompanied by adverse structural brain changes in adolescent drinkers. This scoping review will aim to quantify and evaluate the quality of studies in which magnetic resonance imaging (MRI) techniques are used to assess regional brain deficits among adolescents who consume alcohol.